DOI: 10.26512/2014.12.t.18312
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas e microbiológicas do leite de ovelha e atividade antagonista de sua microbiota lática

Abstract: Ao longo de quatro anos de doutorado, são muitas as pessoas que colaboraram, e a elas espero conseguir transmitir toda a minha gratidão. A Deus acima de tudo, por permitir-me vencer mais esta jornada, dando-me força e saúde. Aos meus pais por todo apoio, educação e incentivo que sempre me prestaram, durante todos os momentos de minha vida. Ao meu marido Fábio por compartilhar comigo seu enorme amor, seu carinho, seu tempo, sua fortaleza, sua paciência. Obrigada por aguentar meus momentos ausentes, obrigada por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(85 reference statements)
0
0
1
Order By: Relevance
“…The results of the antagonist activity of the lactic acid bacteria in the face of the indicator microorganism of the Gram-positive group found in this study are not consistent with the reports found in the scientific literature, which report a satisfactory inhibition of pathogenic microorganisms such as Staphylococcus aureus (Acurcio et al, 2014;Koch et al, 2014;Souza, 2015).…”
Section: Forcontrasting
confidence: 95%
“…The results of the antagonist activity of the lactic acid bacteria in the face of the indicator microorganism of the Gram-positive group found in this study are not consistent with the reports found in the scientific literature, which report a satisfactory inhibition of pathogenic microorganisms such as Staphylococcus aureus (Acurcio et al, 2014;Koch et al, 2014;Souza, 2015).…”
Section: Forcontrasting
confidence: 95%